Notary Role in Issuing Bonding Guarantee of Bilyets Deposits as Collateral Credit on Loan Agreement Process (Case Study in Kanca BRI Blora) - Yongky Pratama; Nanang Suhendar; Achmad Sulchan (Jurnal Akta, 2018)
The purpose of this study was to: 1) Determine the implementation of binding guarantee term deposit certificate as collateral credit on the loan agreement. 2) The role of the notary in binding guarantee term deposit certificate as collateral on the loan agreement. 3) Analyze the challenges and solutions for binding guarantee term deposit certificate as collateral credit on the loan agreement (case study in Kanca BRI Blora). The method is a juridical sociological approach to the specification of descriptive analytical research. Sources of data obtained through interviews and literature.Based on the research results implementation binding guarantee slip deposits as collateral on the loan agreement in BRI Blora starting from the stage of the loan application, the stage of the agreement and the making of the loan agreement, the stage of a deed binding guarantee deposit slip, the submission phase objects assurance, the stage of the authorization, and blocking stage or in the event of default. In binding guarantee term deposit certificate as collateral on the loan agreement in Kanca BRI Blora, Notary make a letter of agreement and binding guarantee deposit slips. Barriers just a lack of understanding about people who do the will of credit, so the solution the Bank must give a detailed explanation before binding treaty process.Keywords : Collateral Credit; Guarantees Binding; Temporary Bilyet Deposits.